Parental stress among parents of children with type 1 diabetes mellitus: a review - Hassouneh, Ola; Nsour, Mona; Lee, Khuan; Al-Oran, Haytham Mohammad (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
This review provides an overview of the evidence which concerns the parental stress of children with type 1 diabetes mellitus. Articles for this review were collected using the Science Direct, CINAHL, PsycINFO, Medline, Scopus, EBSCO, Springer, Ovid, PubMed, Google Scholar, and Cochrane Library. In total, 38 articles were relevant to this review. The findings of the reviewed studies provide an exciting opportunity to advance our knowledge for a different aspect of parental stress which is related to the disease and predictor’s factor contributes to parental stress. This review sheds new light on developing the educational programs to reduce the level of parental stress and to help them to cope positively with this disease.